The children of Noisy Village - Lindgren, Astrid 1907-; Wikland, Ilon. (New York Puffin Books, 1988)
Ten-year-old Lisa tells about her brothers and playmates and the happy times they spend at work and at play in their Swedish village.
Translation of: Bullerbyboken.
Keywords: Family life -- Fiction. -- Sweden; Country life -- Fiction. -- Sweden; Sweden -- Fiction